(untitled) (Research, Society and Development, 2023)
Introduction: Mandibular fractures correspond to approximately 15.5 to 59% of facial fractures, occurring due to local factors that are caused by variations in the positioning of third molars, as well as impaction, which include prolonged retention of deciduous teeth, poor positioning of tooth germs, insufficient dental arch length, supernumerary tooth, odontogenic tumors, abnormal eruption trajectory. Objective: to understand, through a literature review, the relationship between mandibular fractures and the presence or absence of lower third molars. Material and Method: A bibliographic search was carried out in the PUBMED and SCIELO databases, with a maximum of 6 years in the literature. Results: The results showed that the presence of impacted mandibular third molars increased the chances of angular fractures. Missing or fully erupted third molars correlated significantly with condylar fractures. Regarding positions, classes III and C are the most likely to cause mandibular angle fractures. The most favorable third molar positions for condylar fracture are class A and I Conclusion: The presence of impacted mandibular third molars increases the chances of angular fractures and their absence or complete eruption is significantly correlated with condylar fractures. Class III and C positions are more likely to cause mandibular angle fractures.